Adherence of enteropathogenic Escherichia coli to intestinal epithelium in vivo. - Hohmann, A (1975)
Two porcine strains of enteropathogenic Escherichia coli, one possessing K88 antigen and one lacking K88, were orally inoculated into conventional neonatal piglets. Athough both strains caused severe diarrhea, only the K88-possessing strain was able to proliferate in the anterior small intestine. Both K88-possessing and K88-lacking strains were found in large numbers in the posterior small intestine and, using fluorescent antibodies and scanning and transmission electron microscopy, were found adhering to the epitheial surface in these regions. The presence of an unusual surface structure on the bacterial cell of the K88-lacking strain was described.